Improving the sound absorption performance of sustainable thermal insulation materials: Natural hemp fibres. (July 2019) - Santoni, Andrea; Bonfiglio, Paolo; Fausti, Patrizio; Marescotti, Cristina; Mazzanti, Valentina; Mollica, Francesco; Pompoli, Francesco
Abstract: Compared to the traditional synthetic fibrous materials, natural fibres represent sustainable solution to be used either in building construction and noise control engineering and acoustic treatments. Natural fibres are mainly employed in the building industry for their hygrothermal properties, however the possibility to also use them for acoustic purposes would greatly increase their appeal to the market. While synthetic fibres have been studied for almost fifty years, the knowledge of natural fibres is still limited and needs to be expanded. Natural fibres are affected by a large variability of the physical properties, which consequently causes great uncertainty in numerical modelling and difficulties during the design process of acoustics treatments. This study highlights the possibility to enhance the acoustic performance of hemp fibrous materials through the manufacturing process, investigating how each treatments affects the material's physical characteristics and its sound absorption coefficient. Moreover, a simplified model to evaluate the acoustic performance of hemp fibrous materials as a function of their density is proposed, in order to provide a practical tool to investigate and compare different solutions. The physical parameters numerically evaluated for a varying compression rate have been compared with the experimental results, measured at each stage of the production process on samples with a different density and thickness. The global reliability of the proposed approach is finally investigated by comparing the experimental sound absorption for normal incidence with the results obtained from the Johnson-Champoux-Allard model.